Compact microstrip-based textile antenna for 802.15.6 Wban-UWB with full ground plane. - Samal, Purna B.; Zakaria, Zahriladha; Ping, Jack Soh (Hindawi Limited, 2019)
The paper presents the design and investigation of a flexible all-textile antenna operating in the wireless body area network (WBAN) ultrawideband (UWB) specified by the IEEE 802.15.6 standard. The proposed antenna features an innovative and compact UWB radiator on top of the overall structure with a full ground plane on its reverse side. The radiator, which is based on a microstrip patch combined with multiple miniaturization and broadbanding methods, resulted in a simple topology and a compact size of 39 mm × 42 mm × 3 34 mm (0 51 × 0 55 × 0 043λ). In comparison to the literature, the proposed structure is considered to be the most compact microstrip-based textile UWB antenna to date featuring a full ground plane. The choice of the commercial textiles is also made based on cost efficiency, ease of accessibility, and ease of fabrication using simple tools. Meanwhile, the full ground plane enables the antenna operation in the vicinity of the human body with minimal body coupling and radiation towards it, ensuring operational safety. Besides its operation in the mandatory channels of the WBAN-UWB low and high bands, the proposed antenna also operates and preserves its performance in five other optional channels of the high band when placed on the body and under bend conditions of 30° and 60°. The proposed antenna successfully achieved the specific absorption rate below the regulated limit specified by the Federal Communications Commission